2015
DOI: 10.3329/ptcb.v25i1.24124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Nitrate and Amino Acids on High Frequency Plants Regeneration in Barley (Hordeum vulgare L.)

Abstract: Three Bangladeshi barley genotypes viz. BARI barley-1, 3 and 6 were selected for this study to evaluate the efficiency of callus induction and plant regeneration. The effect of five doses of AgNO3 singly, and combined with amino acids (Lproline, L-glutamine) on callus induction and plant regeneration efficiency was evaluated using BARI barley-3 and 6. The maximum values of callus induction were recorded at 49.20 and 32.66% for BARI barley-6 and 3, respectively when 2.0 mg/l AgNO3 and 200 mg/l L-glutamine were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Among many compounds used in the in vitro anther culture, Cu 2+ and Ag + are being considered as promising [53,54]. There are shreds of evidence that the ions may increase the number of green regenerants in cereals [55,56]. However, the action of the ions may depend on their concentration in the medium as the cell wall components, i.e., cellulose may absorb them limiting their availability for the proper functioning of the respiration pathway [57].…”
Section: Discussionmentioning
confidence: 99%
“…Among many compounds used in the in vitro anther culture, Cu 2+ and Ag + are being considered as promising [53,54]. There are shreds of evidence that the ions may increase the number of green regenerants in cereals [55,56]. However, the action of the ions may depend on their concentration in the medium as the cell wall components, i.e., cellulose may absorb them limiting their availability for the proper functioning of the respiration pathway [57].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that microspore developmental stage and some chemical substances in addition to the culture medium influenced the efficacy of embryogenesis in cereal crops [ 16 ]. Moreover, plant growth regulators have been used in induction media that helped for increasing the ability of embryogenesis in anther culture of wheat, rice and barley [ 17 , 18 , 19 ]. Some chemical substances have frequently been reported to prevent accumulation of phenolic compounds and their toxic effects on plant tissue culture phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…AA has been shown to inhibit the browning of cultured tissues and improve morphogenesis in Cavendish banana (Ko et al, 2009) and Brachylaena huillensis (Ndakidemi et al, 2014). Similarly, AgNO 3 is a potent ethylene inhibitor and its presence in culture medium has been reported to inhibit browning and induce in vitro shoot production in many plant species (Haque et al, 2015;Kabir et al, 2013;Mookkan and Andy, 2014). Several hypotheses have been postulated on possible mechanisms of AgNO 3 in reducing explant browning and promoting plant regeneration.…”
mentioning
confidence: 99%